Text of lectures discipline "Compliance Management in the Financial and Credit Sphere" - Yurieva, Iryna (National Technical University "Kharkiv Polytechnic Institute", 2024)
The text of the lectures includes the main issues related to the theory and practice of compliance management in the financial and credit sphere. The discipline is aimed at mastering the theoretical and methodological foundations of the study system, which provides for management measures, prevention and overcoming the risks of non-compliance with the requirements of legislation, rules, policies and standards. At the same time, compliance specialists (compliance officers), as independent officials who analyze appeals about possible cases of corruption or other violations of the law, as well as conduct their own internal investigations, contribute to ensuring the management activities of top management of organizations with identified risks and establishing interaction with both external and internal stakeholders to adapt the developed tools and policies of the organization.
Keywords: text of lectures; risk management in compliance; economic activity; finance; management; compliance in credit institutions; audit; effective models of compliance use; corporate culture; ethical aspects